Primary ovarian insufficiency consequence of autoimmune diseases: a bidirectional two-sample Mendelian randomization study - Du, Yongming; Hu, Yichao; Sheng, Yuehua; Zhu, Tianhong; Liu, Shenping; Ding, Huiqing; Guan, Yutao (Frontiers in Endocrinology, 2024)
Background: Observational studies suggest the risk of primary ovarian insufficiency (POI) is increased in autoimmune disorders (AIDs), but it is unclear whether there is a causal relationship. Therefore, we aimed to investigate the bidirectional causality between 20 AIDs and POI using Mendelian randomization (MR) analysis.Methods: A bidirectional two-sample MR investigation was designed by using publicly accessible summary-level data from genome-wide association studies (GWAS). The inverse variance weighted (IVW) method was performed as the main analysis, supplemented by several sensitivity analyses. Cochran Q test was used to evaluate SNP estimate heterogeneity. MR-Egger and MR-PRESSO methods were utilized to detect horizontal pleiotropy.The MR analyses revealed that genetically determined coeliac disease (CeD) (OR = 1.124, 95% CI 1.033-1.224, P = 0.007), vitiligo (OR = 1.092, 95% CI 1.003-1.188; P = 0.042), systemic lupus erythematosus (SLE) (OR = 1.122, 95% CI 1.030-1.223, P = 0.008), and selective immunoglobulin A deficiency (SIgAD) (OR = 0.866, 95% CI: 0.776-0.967, P = 0.011) exhibited significant causal relationships with POI.We also found suggestive evidence of positive effect of Addison's disease (AD) towards POI (OR5e-6 = 1.076, 95% CI 1.002-1.154, P = 0.043).This comprehensive MR analysis indicated that SLE, CeD, vitiligo, and AD caused an increased risk of POI, SIgAD was associated with a decreased risk of POI. These insights carry profound clinical implications, particularly emphasizing the early intervention for women with AIDs/POI who wish to preserve their reproductive potential or plan for future pregnancies.